CD40 antisense oligonucleotide inhibition of trinitrobenzene sulphonic acid induced rat colitis. Issue 1 (10th December 2004) - Gao, D; Wagner, A H; Fankhaenel, S; Stojanovic, T; Schweyer, S; Panzner, S; Hecker, M
Abstract : Background: CD154/CD40 interactions play a pivotal role both in humoral and cellular immune responses. Their involvement in the pathogenesis of chronic inflammatory bowel disease (IBD) has been revealed by increased expression of CD40 and CD154 in the inflamed mucosa of patients and the therapeutic effects of anti-CD154 antibodies in experimental colitis. Because of adverse side effects however, the use of such antibodies in patients with IBD may be limited. Aims: An alternative approach to blocking CD154/CD40 interactions by employing a CD40 antisense oligonucleotide (ODN) was explored. Results: After sequencing of the rat CD40 gene, five antisense ODNs were designed, of which one (rAS3) effectively downregulated CD40 expression in rat vascular smooth muscle cells as well as the subsequent changes in gene expression in response to CD40 stimulation. The therapeutic potency of rAS3 was evaluated in the 2, 4, 6-trinitrobenzene sulphonic acid (TNBS) induced colitis model of the rat. Single intracolonic injection of a liposomal formulation of rAS3 either prior to or post colitis induction markedly suppressed the inflammatory reaction in these animals monitored both macroscopically and microscopically over one week, while application of a scrambled control ODN had no such effects. Moreover, reverse transcription-polymerase chain reaction analyses revealed reduced expression of vascular cell adhesion molecule 1, interleukin 12 p40, and monocyte chemoatractive protein 1 in the inflamed mucosa, which in turn may have contributed to the decrease in leucocyte infiltration judged by immunohistochemistry. Conclusions: These results suggest that CD40 antisense ODNs effectively interfere with CD154/CD40 interactions in vivo and, therefore, may provide a novel approach to the treatment of patients with chronic IBD.